Η ΘΕΩΡΗΣΗ ΤΟΥ ΠΟΛΙΤΙΚΟΥ ΣΥΣΤΗΜΑΤΟΣ ΤΩΝ ΙΤΑΛΙΚΩΝ ΚΡΑΤΙΔΙΩΝ (Α' ΜΙΣΟ ΤΟΥ 15ου ΑΙΩΝΑ) ΑΠΟ ΤΟΝ ΛΑΟΝΙΚΟ ΧΑΛΚΟΚΟΝΔΥΛΗ - ΠΑΝΝΑΚΟΠΟΥΛΟΣ, ΔΗΜΗΤΡΙΟΣ Κ. (Eoa kai Esperia, 2003)
The Laonikos Chalkokondyles' historical work refers extensively to the socialand political situation of western-european populations in the late medieval era. Thedescription of the Italian peninsula as a geopolitical unity has a main position in thisnarration.This article tries to underpin the special importance, which Laonikos Chalkokondylesattached to the description of the political situation of the Italian cities-states.Apart from this, it makes an effort to document this historiographical selection.Chalkokondyles of course keeps systematically a distance from the events.However, the way that was used by one of the last Byzantine historians in order tomaintain the political system of Italian cities, proves his strong interest about it. Thisinterest is revealed by having a critic spirit and highlighting the possitive sides ofeach regime. It is, also, revealed by expounding at great length. It is significant thatthose features didn't exist in his references to the other european societies.The structure used in this topic is the following:The basic part is an annotation to Chalkokondyles' references regarding thepolitical organisation in the main four city-states, Venice, Genoa, Florence and Milan.The topic is framed by two introductive chapters and conclusions as an epilogue. In thechapters mentioned, Chalkokondyles is incorporated in his contemporary backround.In the same part the Italian urban milieux on the borderline of 14th and 15th centuriesis basicaly described.In the conclusions the central aspect that runs through the way of theChalkokondylean descriptions of Italian cities, is restructed. It is also undertaken toexplain this way from the political view of the historian and his relationship with thatgroup of Despotate of Morea which was friendly to the West.